Review article: the role of gastrointestinal hormones in the treatment of delayed gastric emptying in critically ill patients. Issue 6 (23rd July 2013) - Luttikhold, J.; de, F. M.; van, K.; Diamant, M.; Witkamp, R. F.; van, P. A. M.; Vermeulen, M. A. R.
Summary Background Delayed gastric emptying limits the administration of enteral nutrition, leading to malnutrition, which is associated with higher mortality and morbidity. Currently available prokinetics have limitations in terms of sustained efficacy and side effects. Aim To summarise the mechanisms of action and to discuss the possible utility of gastrointestinal hormones to prevent or treat delayed gastric emptying in critically ill patients. Methods We searched PubMed for articles discussing 'delayed gastric emptying', 'enteral nutrition', 'treatment', 'gastrointestinal hormones', 'prokinetic', 'agonist', 'antagonist' and 'critically ill patients'. Results Motilin and ghrelin receptor agonists initiate the migrating motor complex in the stomach, which accelerates gastric emptying. Cholecystokinin, glucagon‐like peptide‐1 and peptide YY have an inhibiting effect on gastric emptying; therefore, antagonising these gastrointestinal hormones may have therapeutic potential. Other gastrointestinal hormones appear less promising. Conclusions Manipulation of endogenous secretion, physiological replacement and administration of gastrointestinal hormones in pharmacological doses is likely to have therapeutic potential in the treatment of delayed gastric emptying. Future challenges in this field will include the search for candidates with improved selectivity and favourable kinetic properties.